Renormalization of Dirac Delta Potentials Through Minimal Extension of Heisenberg Algebra - Erman, Fatih; Erman, Fatih (IOP Publishing Ltd., 2017)
We renormalize the model of multiple Dirac delta potentials in two and three dimensions by regularizing it through the minimal extension of Heisenberg algebra. We show that the results are consistent with the other regularization schemes given in the literature.
Keywords: Dirac delta potentials; Renormalization; Heisenberg algebra